Interface-reinforced composite current collector and preparation method thereof

By introducing an interface reinforcement layer of alkali metal fluoride into the composite liquid collector, the metal delamination problem caused by poor binding force between the metal layer and the polymer layer is solved, and the conductive performance and interface stability of the current collector are significantly improved.

CN119447318APending Publication Date: 2025-02-14YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411570814.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

Smart Images

  • Figure BDA0005121206530000051
    Figure BDA0005121206530000051
  • Figure BDA0005121206530000061
    Figure BDA0005121206530000061
Patent Text Reader

Abstract

The invention discloses an interface-reinforced composite current collector, which comprises a base film made of a polymer material; the aluminum oxide layer is arranged on the surface of the base film; the interface strengthening layer is arranged on the surface, far away from the base film, of the aluminum oxide layer; the interface strengthening layer contains alkali metal fluoride; the aluminum layer is arranged on the surface, far away from the base film, of the interface strengthening layer. The introduction of the interface strengthening layer can improve the surface performance of the aluminum oxide coating, regulate and control the deposition morphology of the subsequent metal aluminum coating, further improve the binding force between the coatings, and effectively improve the overall interface stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to an interface-strengthened composite current collector and a preparation method thereof. Background Art

[0002] The current collector is an important component of the secondary battery. At present, the positive electrode current collector adopts a composite current collector with a metal-polymer material-metal structure to replace the traditional aluminum foil current collector. The polymer composite metal current collector has obvious advantages in improving the safety of lithium-ion batteries and increasing the energy density of batteries. With the development of vacuum coating, the production process of flexible conductive films has gradually replaced traditional electroplating, coating and chemical treatment methods by vacuum coating. This aluminum-plated composite film prepared by evaporation has good metal properties.

[0003] Compared with traditional aluminum foil, this composite current collector prepared based on vacuum coating has poor bonding between the polymer substrate and the metal coating, which causes the metal coating to easily fall off the substrate surface, which will seriously affect the long-term stability of the current collector in the battery. Therefore, a method of using plasma to treat the substrate surface to improve its roughness and thereby strengthen the bonding between the substrate and the metal coating has been derived. However, the composite current collector prepared based on this strategy still cannot be better solved in the electrolyte environment of lithium-ion batteries due to the poor bonding between the metal layer and the polymer layer, resulting in serious metal delamination. At present, in order to solve the problem of delamination of composite current collectors in the electrolyte, the composite current collector is generally prepared by introducing an intermediate layer such as aluminum oxide / silicon oxide between the substrate and the metal layer. This can, to a certain extent, utilize the bonding effect of polymers on the surface of amorphous aluminum oxide / silicon oxide to improve the bonding strength between the substrate and the metal coating. However, the bonding strength between aluminum oxide and the subsequent metal aluminum coating is poor, which will also lead to problems such as cracking, discontinuity, unevenness or local dealumination of the metal layer to a certain extent. These behaviors will greatly reduce the conductivity of the electrode material and increase the internal resistance of the battery, thereby causing battery safety problems. Summary of the invention

[0004] In order to improve the bonding strength between the aluminum oxide layer and the aluminum layer in the composite current collector and improve the current collector performance, the present invention proposes an interface-strengthened composite current collector and a preparation method thereof. The above-mentioned purpose can be achieved by the following technical solution implementation method:

[0005] An interface-strengthened composite current collector comprising:

[0006] A base film, wherein the base film is made of a polymer material;

[0007] An aluminum oxide layer, wherein the aluminum oxide layer is disposed on the surface of the base film;

[0008] An interface strengthening layer, the interface strengthening layer is arranged on a surface of the aluminum oxide layer away from the base film; the interface strengthening layer contains metal fluoride;

[0009] An aluminum layer is disposed on a surface of the interface strengthening layer away from the base film.

[0010] Optionally, the interface strengthening layer includes at least one of LiF, CsF, RuF, NaF, and KF.

[0011] Optionally, the thickness of the interface strengthening layer is 0.5-3 nm.

[0012] Optionally, the aluminum oxide layer has a thickness of 2-50 nm.

[0013] Optionally, the aluminum layer has a thickness of 0.6-1.5 μm.

[0014] Optionally, the interface strengthening layer is made of LiF and has a thickness of 0.5-2 nm. Optionally, the method comprises the following steps:

[0015] Step 1) depositing an aluminum oxide layer on the base film;

[0016] Step 2) depositing an interface strengthening layer on the aluminum oxide layer;

[0017] Step three) depositing an aluminum layer on the interface strengthening layer to obtain the interface strengthened composite current collector.

[0018] Optionally, the deposition method is vacuum evaporation.

[0019] Optionally, the method for depositing the interface strengthening layer in step 2) is vacuum evaporation coating.

[0020] The technical solution of the present invention has the following advantages:

[0021] (1) The present invention provides an interface-strengthened composite current collector, in which an alkali metal fluoride interface strengthening layer is arranged on the aluminum oxide layer; the alkali metal fluoride interface strengthening layer is located between the aluminum oxide and the metal aluminum coating, and forms a stable strong Al-FO chemical bond with the oxygen-containing functional groups in the aluminum oxide coating and the Al in the aluminum metal coating. The introduction of fluorine-based chemical bonds can improve the surface properties of the aluminum oxide coating, regulate the morphology of the subsequent metal aluminum coating deposition, further improve the bonding force between the coatings, and effectively improve the overall interface stability.

[0022] (2) In the above-mentioned composite aluminum current collector, the alkali metal fluoride interface strengthening layer reacts synergistically with the thicker outer layer of Al to release active metal Li, forming a dual electrode with the metal Al, enhancing its conductivity, and further improving the performance of the current collector. DETAILED DESCRIPTION

[0023] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0024] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0025] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0026] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0027] The present invention provides an interface-strengthened composite current collector, comprising:

[0028] A base film, wherein the base film is made of a polymer material;

[0029] An aluminum oxide layer, wherein the aluminum oxide layer is disposed on the surface of the base film;

[0030] An interface strengthening layer, the interface strengthening layer is arranged on a surface of the aluminum oxide layer away from the base film; the interface strengthening layer contains alkali metal fluoride;

[0031] An aluminum layer is disposed on a surface of the interface strengthening layer away from the base film.

[0032] The interface strengthening layer includes at least one of LiF, CsF, RuF, NaF, and KF.

[0033] The alkali metal fluoride interface strengthening layer is an ultra-thin layer with a thickness of 0.5-3 nm.

[0034] The alkali metal fluoride interface strengthening layer is prepared by vacuum evaporation.

[0035] The preparation method of the above-mentioned composite current collector including an interface strengthening layer includes: first, vapor-depositing an aluminum oxide layer with a thickness of 1-50nm on a polymer base film such as PET / PP, then vapor-depositing an alkali metal fluoride interface strengthening layer with a thickness of 0.5-3nm on the aluminum oxide layer, and finally continuing to vapor-deposit a metal aluminum layer on the ultra-thin interface strengthening layer once or multiple times to form a composite aluminum current collector.

[0036] The thickness of the composite current collector is 3-13 microns.

[0037] The present invention increases the bonding strength between aluminum oxide and the metal aluminum by adding a thin layer of alkali metal fluoride between the aluminum oxide and the metal aluminum coating in the composite aluminum current collector, thereby reducing problems such as discontinuity of the metal layer and local dealumination caused by poor bonding between the coatings, while improving the conductive properties of the composite aluminum current collector, increasing the product yield, and further improving product quality.

[0038] The interface strengthening layer reacts synergistically with a thicker outer layer of Al to release active metal Li, forming a double electrode with the metal Al, enhancing its conductive properties, and further improving the performance of the current collector.

[0039] Embodiment 1:

[0040] The preparation of the composite aluminum current collector containing a 0.5 nm thick interface strengthening layer is as follows:

[0041] (1) A PET film with a thickness of 6 μm was selected as the substrate, placed in the winding system of the vacuum evaporation equipment, and the base film was threaded in the correct direction. Then, the evaporation chamber was vacuumed to ≤9.0×10 -1 Pa. First, a 15 nm thick aluminum oxide layer was deposited on both sides of the PET base film by vacuum evaporation coating, wherein the oxygen flow rate was 1500 sccm, the wire feeding rate was 100 mm / min, and the winding speed was 200 m / min.

[0042] (2) then depositing an ultra-thin LiF interface strengthening layer with a thickness of 0.5 nm on the aluminum oxide coating by vacuum evaporation, wherein the winding speed is 400 m / min and the LiF vapor concentration is maintained at 10 mol / L;

[0043] (3) Finally, a metal aluminum layer with a thickness of 1 μm is deposited on the aluminum oxide coating by vacuum evaporation to form a composite aluminum current collector, wherein the wire feeding rate is maintained at 500 mm / min and the winding speed is 50 m / min.

[0044] Embodiment 2:

[0045] The difference from Example 1 is that the thickness of the LiF interface strengthening layer evaporated in step (2) is 1 nm. The other steps are the same as Example 1.

[0046] Embodiment 3:

[0047] The difference from Example 1 is that the thickness of the LiF interface strengthening layer evaporated in step (2) is 2 nm. The other steps are the same as Example 1.

[0048] Embodiment 4:

[0049] The difference from Example 1 is that in step (2), an ultra-thin CsF interface strengthening layer with a thickness of 0.5 nm is evaporated on the aluminum oxide coating by vacuum evaporation coating, wherein the winding speed is 400 m / min and the CsF vapor concentration is maintained at 10 mol / L. The other steps are the same as in Example 1.

[0050] Embodiment 5:

[0051] The difference from Example 1 is that in step (2), an ultra-thin RuF interface strengthening layer with a thickness of 0.5 nm is evaporated on the aluminum oxide coating by vacuum evaporation coating, wherein the winding speed is 400 m / min and the RuF vapor concentration is maintained at 10 mol / L. The other steps are the same as in Example 1.

[0052] Embodiment 6:

[0053] The difference from Example 1 is that the thickness of the LiF interface strengthening layer evaporated in step (2) is 3 nm. The other steps are the same as Example 1.

[0054] Embodiment 7:

[0055] The difference from Example 1 is that in step (2), an ultra-thin NaF interface strengthening layer with a thickness of 0.5 nm is evaporated on the aluminum oxide coating by vacuum evaporation coating, wherein the winding speed is 400 m / min and the NaF vapor concentration is maintained at 10 mol / L. The other steps are the same as in Example 1.

[0056] Embodiment 8:

[0057] The difference from Example 1 is that in step (2), an ultra-thin KF interface strengthening layer with a thickness of 0.5 nm is evaporated on the aluminum oxide coating by vacuum evaporation coating, wherein the winding speed is 400 m / min and the KF vapor concentration is maintained at 10 mol / L. The other steps are the same as in Example 1.

[0058] Comparative Example 1:

[0059] The preparation of the composite aluminum current collector without an interface strengthening layer is carried out in the following specific steps:

[0060] (1) First, a layer of aluminum oxide was evaporated on the front and back of the PET base film, with an oxygen flow rate of 1500 ppm;

[0061] (2) Then, a metal aluminum layer is evaporated on the aluminum oxide coating once or multiple times to form a composite aluminum current collector.

[0062] Comparative Example 2

[0063] The difference from Example 1 is that the thickness of the LiF interface strengthening layer evaporated in step (2) is 5 nm. The other steps are the same as Example 1.

[0064] Comparative Example 3

[0065] The difference from Example 1 is that in step (2), an ultra-thin CaF2 interface strengthening layer with a thickness of 0.5 nm is evaporated on the aluminum oxide coating by vacuum evaporation coating, wherein the winding speed is 400 m / min and the CaF2 vapor concentration is maintained at 10 mol / L. The other steps are the same as in Example 1.

[0066] Test example:

[0067] The bonding strength is measured by an electronic peeling force tester (model BLD-200H): cut a 120×50mm sample, stick the sample on a steel plate with 3M double-sided tape, roll it, and then stick 3M transparent tape on the sample. After rolling again, place the sample on the fixture of the electronic peeling force tester to test and obtain the sample bonding strength value.

[0068] The square resistance is obtained by testing with a four-probe square resistance meter (model HPS2661): a 200mm sample is cut and placed in the measurement area of ​​the four-probe square resistance meter. Five points are selected for testing and the average value is calculated.

[0069] Table 1 Test results

[0070]

[0071]

[0072] The test results are shown in Table 1. From the comparison between the above examples and the comparative examples, it can be seen that the use of alkali metal fluorides to make the interface strengthening layer can improve the bonding force between the coatings, effectively improve the overall interface stability, and enhance the current collector conductivity, reduce the square resistance, and further improve the performance of the current collector. However, when non-alkali metal fluorides are used or the thickness of the interface strengthening layer is too large, the effect of improving the bonding force and enhancing the conductivity cannot be achieved.

[0073] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.

Claims

1. An interface-strengthened composite current collector, characterized in that: include: A base film, wherein the base film is made of a polymer material; an aluminum oxide layer, wherein the aluminum oxide layer is disposed on the surface of the base film; An interface strengthening layer, the interface strengthening layer is arranged on a surface of the aluminum oxide layer away from the base film; the interface strengthening layer contains an alkali metal fluoride; The aluminum layer is disposed on a surface of the interface strengthening layer away from the base film.

2. The interface-strengthened composite current collector according to claim 1, characterized in that: The interface strengthening layer includes at least one of LiF, CsF, RuF, NaF, and KF.

3. The interface-strengthened composite current collector according to claim 1, characterized in that: The thickness of the interface strengthening layer is 0.5-3 nm.

4. The interface-strengthened composite current collector according to claim 1, characterized in that: The thickness of the aluminum oxide layer is 2-50 nm.

5. The interface-strengthened composite current collector according to claim 1, characterized in that: The thickness of the aluminum layer is 0.6-1.5 μm.

6. The interface-strengthened composite current collector according to claim 1, characterized in that: The interface strengthening layer is made of LiF and has a thickness of 0.5-2nm.

7. The method for preparing an interface-strengthened composite current collector according to any one of claims 1 to 6, characterized in that: The steps include: Step 1) depositing an aluminum oxide layer on the base film; Step 2) depositing an interface strengthening layer on the aluminum oxide layer; Step three) depositing an aluminum layer on the interface strengthening layer to obtain the interface strengthened composite current collector.

8. The method for preparing the interface-strengthened composite current collector according to claim 7, characterized in that: The deposition method is vacuum evaporation.

9. The method for preparing the interface-strengthened composite current collector according to claim 7, characterized in that: The method for depositing the interface strengthening layer in the step 2) is vacuum evaporation coating.

10. Use of the interface-strengthened composite current collector according to any one of claims 1 to 6 in preparing a battery.